Simbologia de açorianidade na pintura de Domingos Rebelo e de Borba Vieira - Castro, Gabriela (2016)
This paper tries to show, through examples from Azores paintings, in particular in the works of Domingos Rebelo and Borba Vieira, some of the fundamental categories of aesthetics and hermeneutics of painting.